Successful validation of genomic biomarkers for human immunotoxicity in Jurkat T cells in vitro. Issue 7 (25th November 2014) - Schmeits, Peter C. J.; Shao, Jia; van der Krieken, Danique A.; Volger, Oscar L.; van Loveren, Henk; Peijnenburg, Ad. A. C. M.; Hendriksen, Peter J. M.
Abstract Previously, we identified 25 classifier genes that were able to assess immunotoxicity using human Jurkat T cells. The present study aimed to validate these classifiers. For that purpose, Jurkat cells were exposed for 6 h to subcytotoxic doses of nine immunotoxicants, five non‐immunotoxicants and four compounds for which human immunotoxicity has not yet been fully established. RNA was isolated and subjected to Fluidigm quantitative real time (qRT)–PCR analysis. The sensitivity, specificity and accuracy of the screening assay as based on the nine immunotoxicants and five non‐immunotoxicants used in this study were 100%, 80% and 93%, respectively, which is better than the performance in our previous study. Only one compound was classified as false positive (benzo‐e‐pyrene). Of the four potential (non‐)immunotoxicants, chlorantraniliprole and Hidrasec were classified immunotoxic and Sunset yellow and imidacloprid as non‐immunotoxic. ToxPi analysis of the PCR data provided insight in the molecular pathways that were affected by the compounds. The immunotoxicants 2, 3‐dichloro‐propanol and cypermethrin, although structurally different, affected protein metabolism and cholesterol biosynthesis and transport. In addition, four compounds, i.e. chlorpyrifos, aldicarb, benzo‐e‐pyrene and anti‐CD3, affected genes in cholesterol metabolism and transport, protein metabolism and transcription regulation. qRT–PCR on eight additional genes coding for similar processes as defined in ToxPi analyzes, supported these results. In conclusion, the 25 immunotoxic classifiers performed very well in a screening with new non‐immunotoxic and immunotoxic compounds. Therefore, the Jurkat screening assay has great promise to be applied within a tiered approach for animal free testing of human immunotoxicity. Copyright © 2014 John Wiley & Sons, Ltd.